2003
DOI: 10.1053/jlts.2003.50242
|View full text |Cite
|
Sign up to set email alerts
|

Osteopenia and osteoporosis in patients with end-stage liver disease caused by hepatitis C and alcoholic liver disease: Not just a cholestatic problem

Abstract: Although best characterized in chronic cholestatic liver disease, osteopenic bone disease and fracturing are wellrecognized complications of cirrhosis, particularly after liver transplantation. We sought to compare the prevalence of osteopenia and osteoporosis, to assess the effect of orthotopic liver transplantation (OLT) on bone density, and to determine fracture rates before and after OLT in three groups of patients with advanced cirrhosis: patients with cirrhosis from hepatitis C virus ( T he association b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(56 citation statements)
references
References 24 publications
3
53
0
Order By: Relevance
“…Various studies over the last 2 decades have shown that the prevalence of osteoporosis in patients with cirrhosis is between 12% and 55% 12,[16][17][18][19][20][21][22][23][24] (Table 2). The difference between studies is probably a reflection of differences in age, liver disease etiology, nutritional state, hypogonadism, and liver disease severity.…”
Section: Cirrhosismentioning
confidence: 99%
“…Various studies over the last 2 decades have shown that the prevalence of osteoporosis in patients with cirrhosis is between 12% and 55% 12,[16][17][18][19][20][21][22][23][24] (Table 2). The difference between studies is probably a reflection of differences in age, liver disease etiology, nutritional state, hypogonadism, and liver disease severity.…”
Section: Cirrhosismentioning
confidence: 99%
“…[20] On the other hand, adiponectin may stimulate proliferation, differentiation and mineralization of osteoblasts. [17] Several studies report osteopenia among patients with HCV infection, [21][22][23][24][25] although possibly osteopenia is rather related to liver function derangement and/or altered nutritional status than to virus infection. In fact, some studies including relatively large series fail to detect significant bone alterations in HCV patients.…”
Section: Introductionmentioning
confidence: 99%
“…Liver cirrhosis itself has been proven to cause a loss of bone mass due to poor cholecalciferol absorption through the intestine, poor activation of vitamin D, and chronic hypogonadism in men (29)(30)(31)(32); however, osteoporosis itself appears insufficient to cause OFH. Interleukin-6 (IL-6) is a proinflammatory cytokine.…”
Section: Discussionmentioning
confidence: 99%